Dietary red pepper ingestion increases carbohydrate oxidation at rest and during exercise in runners - Lim, K.; Yoshioka, M.; Kikuzato, S.; Kiyonaga, A.; Tanaka, H.; Shindo, M.; Suzuki, M. (Medicine & Science in Sports & Exercise, 1997)
The effects of dietary hot red pepper on energy metabolism at rest and during exercise were examined in long distance male runners 18-23 yr of age. A standardized meal was given on the evening prior to the experiment. The subjects had a meal (2720 kJ) with or without 10 g of hot red pepper for breakfast. During rest (2.5 h after meal) and exercise (pedaling for 1 h at 150 W, about 60% VO2max, using cycling ergometry), expired gasses and venous blood were collected. The meal with hot red pepper significantly elevated respiratory quotient and blood lactate levels at rest and during exercise. Oxygen consumption at rest was slightly but nonsignificantly higher in the hot red pepper meal at 30 min after the meal. Plasma epinephrine and norepinephrine levels were significantly higher in those who had only hot red pepper at 30 min after the meal. These results suggest that hot red pepper ingestion stimulates carbohydrate oxidation at rest and during exercise.